Re-discovery of the Giant West African Squeaker, Arthroleptis krokosua Ernst, Agyei & Rödel, 2008 (Amphibia: Anura: Arthroleptidae) in two forests of south-western Ghana with observations on the species’ variability and habitat preferences - Adum, Gilbert Baase; Ofori-Boateng, Caleb; Oduro, William; Rödel, Mark-Oliver (Zootaxa, 2011)
Arthroleptis krokosua Ernst, Agyei & Rödel, 2008 is a recently described, morphologically distinct squeaker species. It has no apparent affiliations to any other West African member of the genus (Ernst et al. 2008), but instead is most closely related to some Central African Arthroleptis (Blackburn et al. 2010). It differs from all known West African Arthroleptis by its large size (> 40 mm snout-vent-length), coloration and other morphological characters, such as a very broad head. Until now the species is only known from the type locality, the Krokosua Hills Forest Reserve and only from the holotype (Ernst et al. 2008). Other large Arthroleptis (larger than 35 mm SVL) are known from Central and East Africa (Blackburn et al. 2009). As A. krokosua might be locally endemic, i.e. amphibian assessments in other Ghanaian and eastern Ivorian forests failed to detect this species (Hillers et al. 2009 and literature cited therein); we herein aim to add more data on the variability, distribution and ecology of A. krokosua.